Securing decarbonized road transport – a comparison of how EV deployment has become a critical dimension of battery security strategies for China, the EU, and the US - Loyle Campbell; Manfred Hafner; Xinqing Lu; Michel Noussan; Pier Paolo Raimondi; Erpu Zhu (Fondazione Eni Enrico Mattei (FEEM), 2021)
This paper compares how the pursuit of self-sufficient Lithium-ion battery production by the three main geo-economic players (China, the European Union, and the United States) is unfolding by looking at the electrification of the transport sector. The analysis of this paper uses the concept of energy security and the 4 As outlined by the Asia Pacific Energy Research Center (2007) to outline the availability, accessibility, affordability, and acceptability of Lithium-ion (Li-Ion) batteries for each respective actor. This paper aims to compare the dynamics of each geoeconomic player's EV deployment along these four indicators. Most work in this field assesses the battery strategies of these three geo-economic players individually or focuses on EV deployment from a purely economics perspective. In contrast, this paper attempts to bridge this gap through the framework of energy security to compare how each of the three player's battery strategy connects to broader EV deployment. Adopting this framework allows us to highlight how China's strong industrial policies and generous incentives contrast to the government multilateral alliance-building done in the European Union and the overwhelmingly dominant role of private actors found in the United States.
Keywords: Q48; Q30; F59; 330; Lithium-Ion Batteries; Electric Vehicles; Energy Transition; Energy Security; China; the European Union; the United States